2010
DOI: 10.1308/147363510x12779829582415
|View full text |Cite
|
Sign up to set email alerts
|

The urological foot soldier: are we equipping our foundation-year doctors?

Abstract: Tomorrow's Doctors was first published by the General Medical Council (GMC) in 1993. The recommendations provide a framework for UK medical schools to use to design detailed curricula and schemes of assessment in the training of future doctors. They also set out the minimum standards that are used to judge the quality of undergraduate teaching. In 2003 this guidance was revised and a further 2009 version has now been published. A constant feature of these important documents is a list of therapeutic procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 2 publications
2
25
0
Order By: Relevance
“…10 It is difficult to replicate UC insertion in the simulation setting and the current models do not provide typical challenges encountered in a living patient, such as urethral tortuosity in males with its angulations, enlarged prostate, high bladder neck, and possibility of false passage with greater insertion forces. Limitations with conventional simulation models highlight the need for the development of more representative UC simulation models and designs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It is difficult to replicate UC insertion in the simulation setting and the current models do not provide typical challenges encountered in a living patient, such as urethral tortuosity in males with its angulations, enlarged prostate, high bladder neck, and possibility of false passage with greater insertion forces. Limitations with conventional simulation models highlight the need for the development of more representative UC simulation models and designs.…”
Section: Discussionmentioning
confidence: 99%
“…9 This lack of confidence and insufficient experience is reflected by the fact that one in five first-year U.K. interns had never performed male catheterization and nearly half (45%) had never performed a female catheterization after one year of medical practice. 10 Studies on iatrogenic UC injuries tend to focus on interns and interventions for prevention are usually aimed at this grade of healthcare professional. Increasing clinical experience is thought to reduce the chance of causing an iatrogenic UC injury.…”
Section: Discussionmentioning
confidence: 99%
“…Cetti et al found that one in five interns had never performed male UC and nearly half had never performed female UC [3]. This is despite the UK's General Medical Council including urethral catheterization in male and female patients as a minimum standard in those completing medical school [15].…”
Section: Discussionmentioning
confidence: 99%
“…Poor technique can result in potentially avoidable iatrogenic UC-related morbidities such as prolonged catheterization, urethral strictures, urinary incontinence and erectile dysfunction [1]. Studies have questioned whether junior doctors receive adequate training before independent catheterization [2,3]. It has been shown that focused catheterization training before the start of the intern year can significantly reduce the rates of catheter morbidity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…7 Before the pandemic there was arguably already a relative lack of undergraduate training in urology, 8,9 with many junior doctors feeling a lack of confidence in performing basic urological clinical skills such as catheterisation. [10][11][12] The current reduction in exposure to urology at medical student level may exacerbate this lack in training. Delaying recruitment and allowing students time to complete urology placements may be the best way forward.…”
Section: Medical Studentsmentioning
confidence: 99%